Identification of the receptor tyrosine kinases (RTKs)‐oriented functional targets of miR‐206 by an antibody‐based protein array. Issue 16 (2nd July 2015) - Cui, Yazhou; Xie, Shuyang; Luan, Jing; Zhou, Xiaoyan; Han, Jinxiang
Abstract : This study demonstrated the feasibility and benefit of an antibody‐based experimental approach to identify microRNA functional targets from hundreds of predicted genes using miR‐206 as an example. Using a receptor tyrosine kinase (RTK) antibody array, we identified 7 phosphorylated RTKs that were significantly differentially regulated after miR‐206‐mimic transfection. We then focused on MET, the most varied RTK, and bioinformatically constructed a MET‐centred network using computationally predicted miR‐206 targets. Within this network, we analyzed two validated targets, PAX3 and SNX2, and one candidate target, EIF4E, may account for the inhibitory effect of miR‐206 on MET phosphorylation. Luciferase and Western‐blot assays indicated that EIF4E was a direct target of miR‐206. This concept may also be applicable for other microRNAs and other antibody array platforms. Abstract : Protein microarrays can be used to identify functional gene targets of microRNAs. EIF4E is a novel target gene of miR‐206. miR‐206 can suppress MET activation by targeting multiple genes.